2021
DOI: 10.1002/lary.29934
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Barriers Affect Follow‐Up Care in Head and Neck Cancer

Abstract: Objectives/Hypothesis Follow‐up care in head and neck cancers (HNC) is critical in managing patient health. However, social determinants of health (SDOH) can create difficulties in maintaining follow‐up care. The study goal is to explore how SDOH impacts maintenance of HNC follow‐up care appointments. Methods A systematic retrospective chart review of 877 HNC patients diagnosed in the past 10 years a safety‐net tertiary care hospital with systems to help reduce care disparities. Cohort groups were identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Distance from the treating hospital was found to be negatively associated with adherence to follow‐up for HNC care, longer treatment package time, and higher mortality rates 35,42,53,65‐67 . It is important to note that variables such as drive time and travel distance were defined differently among studies and thus, may not be directly comparable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distance from the treating hospital was found to be negatively associated with adherence to follow‐up for HNC care, longer treatment package time, and higher mortality rates 35,42,53,65‐67 . It is important to note that variables such as drive time and travel distance were defined differently among studies and thus, may not be directly comparable.…”
Section: Resultsmentioning
confidence: 99%
“…Distance from the treating hospital was found to be negatively associated with adherence to follow-up for HNC care, longer treatment package time, and higher mortality rates. 35,42,53,[65][66][67] It is important to note that variables such as drive time and travel distance were defined differently among studies and thus, may not be directly comparable. For example, some studies evaluated drive time while others evaluated public transit time, walking distance, or distance directly from point A to point B (as the crow flies).…”
Section: Transportation and Distance To Treatmentmentioning
confidence: 99%
“…While there are numerous considerations, little is known about the interplay between clinical factors, access to healthcare, and socioeconomic biases in making these decisions. Prior studies have shown a correlation between outcomes in head and neck cancer and socioeconomic factors such as race, education, geography, and insurance status 4–10 . To date, this is the first study that addresses these social determinants of health (SDoH) and compliance with NCCN guidelines for therapy for this cancer subsite.…”
Section: Introductionmentioning
confidence: 93%
“…Prior studies have shown a correlation between outcomes in head and neck cancer and socioeconomic factors such as race, education, geography, and insurance status. [4][5][6][7][8][9][10] To date, this is the first study that addresses these social determinants of health (SDoH) and compliance with NCCN guidelines for therapy for this cancer subsite. This is especially important since hypopharyngeal malignancy has the lowest survival rate of all head and neck cancer sites.…”
mentioning
confidence: 99%
“…To date, exercise-based interventions have largely been medical center-based, which may not be feasible or sustainable for long-term survivors [ 7 9 ]. This is especially relevant for survivors who may have geographic constraints or those who are frail and may not be independent enough to travel to the medical center [ 10 – 12 ]. Thus, novel approaches are needed to overcome the limitations of conventional exercise interventions.…”
Section: Introductionmentioning
confidence: 99%